Bacteriological profile and antimicrobial susceptibility pattern of eskape pathogens in blood culture isolated from a tertiary care centre - SUGANTHA VALLI.M; S.S.M.UMAMAGESWARI; M.KALYANI (International Journal of Pharma and Bio Sciences, 2017)
Bacteraemia and septicaemia are a major health problem, which leads to high morbidity and mortality of patients. Timely diagnosis and appropriate medication will be the best way to save the lives of affected ones. The aim of the present study was to determine the bacterial profile of suspected bacteraemia cases and antibiotic susceptibility pattern of ESKAPE pathogens. This is a retrospective study of 3684 blood samples collected from clinically suspected cases of bacteraemia, over a period of two years (April 2015 to March 2017). The isolates were identified by conventional biochemical tests and antimicrobial susceptibility testing by CLSI guidelines. Positive cultures were obtained in 240 (6.5%) cases of which ESKAPE organisms accounted for 66% of cases with Pseudomonasaeruginosa 34% (81) predominance, non ESKAPE organisms accounted were 34% of cases with E. coli 15% (36) predominance and one fungal isolates. Antibiotic resistant pattern among ESKAPE pathogens were, among Enterococcus faecium only one was resistant to vancomycin, among Staphylococcus aureus Methicillin esistant taphylococcus aureus resistant was observed. Klebsiella spp resistant to piperacillin tazobactam and cefaperazone sulbactum, Acinetobacter baumannii and P. aeruginosa ciprofloxacin showed highest activity followed by cefoperazone and sulbactum. Enterobacter spp showed no resistance. This study highlights the health crisis & emergence of ESKAPE pathogens as predominant cause of bacteraemia. It is necessary that the last remaining antimicrobial agents be protected via intellectual choice and ameliorated infection control. Prescription of the most appropriate antibiotics at the right dose and period will consistently improve the sick and decrease the appearance of antibiotic resistance.